Knowledge and Premarital Sexual Behavior among Adolescents at Vocational High Schools in Surakarta: A Cross-Sectional Study - Ariyanti, Lilik; Atur Semartini (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Sexual behavior among adolescents poses serious risks to their physical health, psychological development, and social well-being. Previous studies have consistently reported the occurrence of premarital sexual behavior among adolescents. Adequate knowledge is generally expected to play a preventive role by discouraging adolescents from engaging in premarital sexual practices. Objective: This study aims to examine the relationship between knowledge and premarital sexual behavior among adolescents at Vocational High School in Surakarta. Method: An analytical observational study with a cross-sectional design was conducted among students aged 16–17 years selected through simple random sampling. Data were collected using a structured questionnaire assessing behaviors indicative of sexual activity. Responses were scored using a five-point Likert scale with reverse scoring for negative statements. Total scores of 7–21 indicated risky sexual behavior, whereas scores >21 indicated non-risky behavior. Most respondents demonstrated a good level of knowledge. Result and Discussion: The majority of respondents demonstrated a good level of knowledge. 3.4% of respondents engaged in risky sexual behavior, while 96.6% exhibited non-risky sexual behavior. The analysis of the relationship between knowledge and risky sexual behavior yielded a p-value greater than 0.05, indicating that there was no significant association between knowledge and adolescent sexual behavior. Conclusions: There was no significant relationship between knowledge and premarital sexual behavior among adolescents.